Comparative analysis of gene expression profiles between cortex and thalamus in Chinese fatal familial insomnia patients - Tian, Chan; Liu, Di; Sun, Qing-Lan; Chen, Chen; Xu, Yin; Wang, Hui; Xiang, Wei; Kretzschmar, Hans A.; Li, Wei; Chen, Cao; Shi, Qi; Gao, Chen; et al. (Molecular Neurobiology, 2013)
Fatal familial insomnia (FFI) is a special subtype of genetic human prion diseases that is caused by the D178N mutation of the prion protein gene (PRNP). According to the surveillance data from 2006, FFI accounts for about half of all genetic prion disease cases in China. In this study, global expression patterns of the thalamus and parietal cortex from three patients with FFI were analyzed by Affymetrix Human Genome U133+ 2.0 chip. A total of 1,314 genes in the thalamus and 332 ones in the parietal lobe were determined to be differentially expressed genes (DEGs). The percentage of upregulated DEGs is much less in the thalamus (19.3 %) than that in the parietal lobe (42.8 %). Moreover, 255 of those DEGs showed the same altering tendencies in both tested regions, including 99 upregulated and 156 downregulated ones. The reliability of the results was confirmed by the real-time RT-PCR assays. There were 1,152 and 531 biological processes affected in the thalamus and the parietal lobe, respectively, as well as 391 overlapping ones in both regions. The most significantly changed molecular functions included transcription and DNA-dependent regulation of transcription, RNA splicing, mitochondrial electron transport, etc. The changed functions in the thalamus contained more numbers of DEGs than parietal lobe. According to KEGG classification, there were 167 and 115 different pathways changed in the thalamus and the parietal lobe, respectively, while 102 were changed in both. Interestingly, the top three changed pathways in the three groups mentioned above were Parkinson's disease, Alzheimer's disease, and oxidative phosphorylation. These results demonstrate the greater damage in the thalamus than in the parietal lobe during FFI pathogenesis, which is consistent with previous pathological observations. This study aims to describe the global expression profiles in various brain regions of FFI while proposing useful clues for understanding the pathogenesis of FFI and selecting potential biomarkers for diagnostic and therapeutic tools.
EVALuna2:4687